Enlightening the malaria parasite life cycle: bioluminescent Plasmodium in fundamental and applied research - Siciliano, Giulia; Alano, Pietro (Frontiers in Microbiology, 2015)
The unicellular protozoan parasites of the genus Plasmodium impose on human health worldwide the enormous burden of malaria. The possibility to genetically modify several species of malaria parasites represented a major advance in the possibility to elucidate their biology and is now turning laboratory lines of transgenic Plasmodium into precious weapons to fight malaria. Amongst the various genetically modified plasmodia, transgenic parasite lines expressing bioluminescent reporters have been essential to unveil mechanisms of parasite gene expression and to develop in vivo imaging approaches in mouse malaria models. Mainly the human malaria parasite Plasmodium falciparum and the rodent parasite Plasmodium berghei have been engineered to express bioluminescent reporters in almost all the developmental stages of the parasite along its complex life cycle between the insect and the vertebrate hosts. Plasmodium lines expressing conventional and improved luciferase reporters are now gaining a central role to develop cell based assays in the much needed search of new antimalarial drugs and to open innovative approaches for both fundamental and applied research in malaria.